Removal of Zinc From Circum-Neutral pH Mine-Impacted Waters Using a Novel “Hybrid” Low pH Sulfidogenic Bioreactor - Holanda, Roseanne; Johnson, David Barrie (Frontiers in Environmental Science, 2020)
Environmental pollution associated with metal-contaminated waters discharging from abandoned mine sites is a global issue. Remediation using passive systems, such as constructed wetlands, has several significant detractions which active treatment systems that harness the abilities of hydrogen sulfide-generating bacteria to immobilise transition metals and ameliorate pH can obviate, including the potential for recovering and recycling metals. Here we describe the commissioning and testing of a laboratory-scale, continuous flow “hybrid” sulfidogenic bioreactor (HSB) where both elemental (zero-valent) sulfur (ZVS) and sulfate were provided as potential electron acceptors and glycerol as the primary electron donor for the bacterial consortium immobilised in the bioreactor vessel. The consortium included several species of acid-tolerant bacteria that catalyse the dissimilatory reduction of both ZVS and sulfate, and a novel acidophilic ZVS-reducing Firmicute, distantly related to known sulfidogens. The HSB was used to remediate synthetic and actual circum-neutral pH, zinc-contaminated water bodies from two abandoned metal mining sites in the U.K.. In both cases, zinc was successfully (> 99 %) removed from solution as a sulfide (ZnS) phase using both in-line (where mine water was pumped directly into the bioreactor) and off-line (where hydrogen sulfide was transferred from the HSB to a separate contactor vessel containing the mine waters) configurations. Both mine waters contained sufficient alkalinity to effectively neutralise the generation of acidity resulting from ZnS formation. A potential scenario for full-scale treatment of one of the mine waters using a HSB is described.